The Icelandic bubble and beyond : investment lessons from history and cultural effects - Már Wolfgang Mixa 1965- (2016)
The research project focuses on investment behavior and the Icelandic economic bubble and crash, emphasizing that investment behavior has to be seen within a historical and cultural environment. As such the project is related to financial history and behavioral finance. The project’s main goals can be summarized into the following key research question: What cultural conditions shaped the appearance and formation of the financial bubble in Iceland and in what way did those conditions differ, if any, from other countries and to what extent? The main results are that cultural conditions influenced the creation of the Icelandic banking miracle that ended so badly. Certain dimensions in the Icelandic culture were more suspect of embracing values that (temporarily) opened doors to possibly naïve beliefs. Technological and ideological changes on an international level also influenced the Icelandic culture; more than most cultural studies anticipate. Some changes in the Icelandic culture were, however, caused to a certain extent by design, even an invented cultural one, rather than default. With the use of the media some agents convinced the Icelandic country that their best interests were served blindly embracing certain values when in fact those agents were reaping the profits with speculation and risk taking that the public was eventually left to face the consequences of.